Blessed unrest how the largest movement in the world came into being, and why no one saw it coming - Hawken, Paul. (New York Viking, 2007)
Blessed Unrest tells the story of a worldwide movement that is largely unseen by politicians or the media. Hawken, an environmentalist and author, has spent more than a decade researching organizations dedicated to restoring the environment and fostering social justice. From billion-dollar nonprofits to single-person causes, these organizations collectively comprise the largest movement on earth. This is a movement that has no name, leader, or location, but is in every city, town, and culture. It is organizing from the bottom up and is emerging as an extraordinary and creative expression of people?s needs worldwide.
Includes bibliographical references (p. [321]-330) and index.
Keywords: Environmentalism